Synthesis of end-functionalized phosphate and phosphonate-polypeptides by ring-opening polymerization of their corresponding N-carboxyanhydride - Das, Soumen; Kar, Mrityunjoy; Sen Gupta, Sayam (Polymer Chemistry, 2013)
Phosphopolypeptides provide an interesting biomimetic analog for phosphorylated proteins that are involved in biomineralization. We have developed a high yielding synthesis of cysteine-based phosphate and phosphonate N-carboxyanhydride (NCA) by using the thiol-ene coupling reaction. These phosphate and phosphonate NCA monomers underwent polymerization using simple primary amine initiators to form well defined homophosphopolypeptides. Using a bifunctional initiator we were able to install a ``clickable'' alkyne or azide group at the end of the polypeptide chain. We were also able to successfully synthesize fully water-soluble phosphonate based polypeptides by hydrolysis of the corresponding phosphonate ester groups in the polypeptide. These water-soluble phosphopolypeptides adopt a random coil conformation at physiological pH.